Open and endovascular thoracic aortic repair in patients with end-stage renal disease. (1st July 2019) - Tsubota, Hideki; Sakaguchi, Genichi; Marui, Akira
Abstract: OBJECTIVES: The number of end-stage renal disease (ESRD) patients has increased, but there have been few reports of thoracic aortic surgery in patients with ESRD. The purpose of this study was to evaluate the early and late outcomes of open and endovascular thoracic aortic repairs in patients with ESRD. METHODS: A total of 36 patients with ESRD who needed chronic haemodialysis undergoing open surgery ( n  = 21) or thoracic endovascular aortic repair (TEVAR) ( n  = 15) of the thoracic aorta from 2007 to 2017 in our hospital were identified. Primary end points were in-hospital mortality and late survival; secondary end points were perioperative complications and late aortic events. RESULTS: Fourteen patients (39%) had aortic dissection, and 16 (44%) had aortic aneurysms. Emergency surgery was performed in 12 patients (33%). There were 3 hospital deaths (8%) (open surgery, n  = 1, 5%; TEVAR, n  = 2, 13%). The TEVAR group had fewer transfusions than the open surgery group and shorter intensive care unit and hospital stays. The 1-, 3- and 5-year survival rates were 79%, 58% and 40%, respectively, for patients overall. Freedom from aortic events at 1 and 3 years was 97% and 92%, respectively. CONCLUSIONS: The early outcome of thoracic aorta surgery in patients with ESRD was acceptable. However, the long-term mortality in patients with ESRD was still poor. Therefore, whether to perform surgery needs to be considered carefully.